Dispensing of antibiotics, antitussives and mucolytics to asthma patients: a pharmacy-based observational survey. - Laforest, L; Van Ganse, E; Devouassoux, G; El Hasnaoui, A; Osman, L; Bauguil, G; Chamba, G (2008)
BACKGROUND: Antibiotics, antitussives and mucolytics are commonly used in asthma, despite limited evidence for their effectiveness. The correlates of use for these medication classes in asthma were identified. METHODS: Asthma patients aged 18-50 who were regular customers of pharmacies were included in an observational study. Patients completed a questionnaire, which was complemented by computerised pharmacy records of previously dispensed medications. Users of each drug class were compared to non-users in terms of demographics, asthma characteristics and management. RESULTS: Among 886 patients (mean age: 37; 55% females), 63.2%, 55.8% and 27.2%, respectively, were users of antibiotics, mucolytics and antitussives during the previous 12 months. In multivariate analysis, dispensing of >2 units of oral corticosteroids was the major correlate of receiving antibiotics (OR=5.47; 95% CI=[3.00-9.97]), mucolytics (OR=3.93; 95% CI=[2.38-6.50]) and antitussives (OR=1.86; 95% CI=[1.18-2.94]). Compared to well-controlled patients, the probability of receiving antibiotics was significantly higher for poorly controlled patients (OR=2.01; 95% CI=[1.28-3.15]). CONCLUSIONS: Our results suggest that these drugs are mainly used during asthma exacerbations. A better understanding of the use of co-medication in asthma is required.